Pendampingan Siswa Melalui Penerapan Model Pembelajaran Koopertif Tipe NHT Untuk Meningkatkan Hasil Belajar Fisika di Pondok Pesantren Khairul Fatihin Nahdlatul Wathan Jineng Lombok Timur - Ana Nurhasanah Ana; Hani Ardiyantini; Bidianto; Hasim Rahman; Firman Ali Rahman (Prodi Tadris IPA Biologi UIN Mataram, 2023)
Education is a conscious and planned effort to create a learning atmosphere and learning process so that students actively develop their potential to have religious spiritual strength, selfcontrol, personality, intelligence, noble character, and the skills needed by the people of the nation and state. One of the learning models that actively involve the role of students is the NHT type cooperative learning model. The purpose of this study is to find out how the influence of the NHT type learning model on student learning activities, and how students respond to the NHT type of cooperative learning model. This research method is Classroom Action (CAR). The subjects of this study were class XI students with a total of 37 students. Location This research was carried out at the Khairul Fatihin NW Islamic Boarding School. This research was carried out on July 20, 2023. Student learning outcomes in this implementation were able to improve students' skills and learning abilities. The observation results show that NHT learning can improve student learning outcomes and presentations. Based on the results of the tests that have been carried out, the scores that were originally obtained by students in physics subjects which were initially 50% increased to 80%. The acquisition of evaluation test scores based on the posttest experienced a lot of increase in their learning outcomes